2011
DOI: 10.1161/atvbaha.111.232231
|View full text |Cite
|
Sign up to set email alerts
|

Focal Adhesion Kinase Regulates Smooth Muscle Cell Recruitment to the Developing Vasculature

Abstract: Objective The investment of newly formed endothelial cell tubes with differentiated smooth muscle cells (SMC) is critical for appropriate vessel formation, but the underlying mechanisms remain unknown. We previously showed that depletion of focal adhesion kinase (FAK) in the nkx2.5 expression domain led to aberrant outflow tract (OFT) morphogenesis and strove herein to determine the cell types and mechanisms involved. Methods and Results We crossed fakloxp targeted mice with available Cre drivers to deplete … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Focal adhesions are essential for maintaining structural integrity of vessels by inducing cytoskeletal rearrangements and alignment of vSMCs in response to mechanical strain. Previous studies have shown that genetic deletion of FAK (Ptk2) in vSMC precursors leads to defects in the patterning of the aortic arch arteries and septation of the heart and outflow tract (Hakim et al, 2007;Vallejo-Illarramendi et al, 2009;Cheng et al, 2011). These defects, however, are caused by abnormal recruitment (Hakim et al, 2007;Cheng et al, 2011) and/or impaired differentiation of vSMCs (Vallejo-Illarramendi et al, 2009), neither of which was seen in our mutants.…”
Section: Role Of α5 and αV Integrins In Cardiovascular Developmentcontrasting
confidence: 46%
“…Focal adhesions are essential for maintaining structural integrity of vessels by inducing cytoskeletal rearrangements and alignment of vSMCs in response to mechanical strain. Previous studies have shown that genetic deletion of FAK (Ptk2) in vSMC precursors leads to defects in the patterning of the aortic arch arteries and septation of the heart and outflow tract (Hakim et al, 2007;Vallejo-Illarramendi et al, 2009;Cheng et al, 2011). These defects, however, are caused by abnormal recruitment (Hakim et al, 2007;Cheng et al, 2011) and/or impaired differentiation of vSMCs (Vallejo-Illarramendi et al, 2009), neither of which was seen in our mutants.…”
Section: Role Of α5 and αV Integrins In Cardiovascular Developmentcontrasting
confidence: 46%
“…Focal adhesion kinase has been reported to play a role in the proliferation and migration of aortic smooth muscle cells, and the regulation of smooth muscle cell recruitment during blood vessel morphogenesis . Myo1e has previously been reported to induce FAK phosphorylation and FAK kinase activity .…”
Section: Resultsmentioning
confidence: 99%
“…Heim et al reported that Myo1e binds to the FERM domain of focal adhesion kinase (FAK), activating FAK and inducing Y397 phosphorylation. Previous studies revealed that FAK is involved in the regulation of aortic smooth muscle cell motility and growth, and the regulation of smooth muscle cell recruitment during blood vessel morphogenesis . The potential role of Myo1e and FAK activation in VSMCs in response to MSC‐Exo‐derived signals was also investigated in this study.…”
Section: Introductionmentioning
confidence: 89%
“…The inhibitory effect of SCARA5 on growth has been ascribed to the binding of FAK, which in turn inhibits downstream src-p130Cas activity 9 . In this regard, a study of smooth muscle cells reported that targeted knockout of FAK did not influence cell growth 12 , which appears to preclude a role for FAK in the inhibitory effect of SCARA5. However, Ojala et al reported that expression of SCARA5 in mice is limited to specific populations of fibroblasts in the interstitial space of most organs and is not found in smooth muscle alpha actin positive cells 7 .…”
Section: Discussionmentioning
confidence: 99%